KEBUTUHAN MANUSIA TERHADAP DAKWAH DAN FILSAFAT - Ashadi Cahyadi (JURNAL ILMIAH SYI'AR, 2013)
In Human nature wants “Unity Himself” with God, because that movement and human life is a journey of spiritual evolution towards and closer to the Creator. Humans have two elements, namely physical and spiritual, therefore both should be able to provide to their individual needs. Physical needs food and so does the spiritual, physical if the food is to be the opposite Material is non-material food Ruhani One with the propaganda. If Man can not fulfill his spiritual needs of the Human Body and it will feel Restlessness, troubled and down in the mouth and it is certainly contraryto his nature as a human being endowed with aqal and Qalbu. Humans inprinciple requires Da’wah and Philosophy. Between propaganda and philosophy are like two sides of a coin that can not be split. Whoever the person, without preaching human being into the path of darkness & Heading to the brink of collapse. Da’wah does not need humans but humans who need preaching to the happiness the world and the hereafter. Therefore Philosophy Not Have Meaning, If Not In Inform, Not Manifests Instead Propagation, When Not Bringing Truth